OPTIMASI KINERJA TURBIN PELTON RESPON KEMIRINGAN BUCKET - Din Aswan Ritonga; Junaidi Junaidi; Rizky Gunawan (Universitas Harapan Medan, 2020)
Water is a source of energy that can be used as a power plant by utilizing its potential power. Hydroelectric power plant (PLTA) is a technology that has been proven to be environmentally friendly and does not damage the environment. The use of the turbine depends on the potential head it has. As in this case the Pelton turbine which uses the impulse principle requires a fairly high head. This type of turbine works by utilizing falling water or head, flow velocity, blade angle, number of nozzles, flow size and number of blades. Pelton turbine testing with several combinations of parameters including: nozzle diameter, number of nozzles, number of blades, and blade slope. Optimization analysis using Statistical Software. Based on tests or research conducted on Pelton turbines by varying the bucket slope, number of buckets, diameter of nozzles and number of nozzles using the Taguchi method, it can be concluded that the efficiency of the turbine using 2 nozzles that have been managed for maximum turbine efficiency is produced with a power of 460 watts with efficiency of 28%, found at a bucket slope of 80 at a nozzle diameter of 19 mm. While the maximum turbine efficiency is generated with a power of 220 watts at a bucket slope of -80 with a turbine efficiency of 6% at a nozzle diameter of 25 mm. The maximum output power of the Pelton turbine is by testing using 2 nozzles with a water flow of 375 l/minute at a head of 8 m with a power of 490.5 watts. Based on the results of the Pelton Turbine Test Graph using the Taguchi method, the response of the bucket slope with the Maximum Rotation Nozzle Diameter is at -80 Bucket Inclination Producing a Turbine Rotation of 416.7 Rpm with a Nozzle Diameter of 19 mm. Meanwhile, with a maximum power of 80 bucket slope, it produces a turbine load of 405 watts with a diameter of 22 mm.